On the dynamic behavior of the current in the condenser of a boost converter controlled with ZAD - Darío Del Cristo Vergara Perez; Simeón Casanova Trujillo; Fredy Edimer Hoyos Velasco (Universitas Ahmad Dahlan, 2020)
In this paper, an analytical and numerical study is conducted on the dynamics of the current in the condenser of a boost converter controlled with ZAD, using a pulse PWM to the symmetric center. A stability analysis of periodic 1T-orbits was made by the analytical calculation of the eigenvalues of the Jacobian matrix of the dynamic system, where the presence of flip and Neimar–Sacker-type bifurcations was determined. The presence of chaos, which is controlled by ZAD and FPIC techniques, is shown from the analysis of Lyapunov exponents.